The Role of the Fisheries Subsector in the Regional Economy of Tolitoli Regency - Fitri S. Kasim; Fatimah; Rifay, Riski Thamrin G.; Syafitri, Euis (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study was to determine the role of the fisheries subsector in the regional economy of Tolitoli Regency in 2018-2022. The type of research used is quantitative research with technical analysis of Location Quotient (LQ) analysis data with secondary data obtained from the Tolitoli Regency Central Statistics Agency (BPS). The results of this study indicate that the production of the Tolitoli Regency fisheries subsector according to the calculation of Location Quotient (LQ) analysis shows an average value for 2018-2022 of 0.69 which means less than 1 (LQ <1) and is included in the criteria for non-base or non-leading sectors, it can be said that the fisheries subsector has a role as a local economic sector in the regional economy of Tolitoli Regency in 2018-2022